2016
DOI: 10.1123/jpah.2015-0219
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Behavioral Intervention Increases Maternal Exercise but Does Not Prevent Excessive Gestational Weight Gain in Previously Sedentary Women

Abstract: Sedentary pregnant women should increase PA but may need additional dietary counseling to prevent excessive GWG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
86
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(88 citation statements)
references
References 0 publications
0
86
0
2
Order By: Relevance
“…67686970717273747576777879808182838485868788 A further 45 trials (9945 women)8990919293949596979899100101102103104105106107108109110111112113114115116117118119120121122123124125126127128129130131132133 were identified after the IPD acquisition timeline until February 2017.…”
Section: Resultsmentioning
confidence: 99%
“…67686970717273747576777879808182838485868788 A further 45 trials (9945 women)8990919293949596979899100101102103104105106107108109110111112113114115116117118119120121122123124125126127128129130131132133 were identified after the IPD acquisition timeline until February 2017.…”
Section: Resultsmentioning
confidence: 99%
“…The intervention group participants were aged between 24 and 36 years, whereas the participants from the control groups were aged between 24 and 35 years. Several of the included studies [ 33 , 35 , 36 , 39 , 40 , 41 ] provided measures of prepregnancy body mass index (BMI) with values ranging from 26 to 30 kg/m 2 for the intervention groups and 25 to 30 kg/m 2 for the control groups. Participant ethnicity varied between the studies and study arms (white: intervention: 12.5%-100%; control: 13.3%-100%) [ 33 - 36 , 38 - 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several of the included studies [ 33 , 35 , 36 , 39 , 40 , 41 ] provided measures of prepregnancy body mass index (BMI) with values ranging from 26 to 30 kg/m 2 for the intervention groups and 25 to 30 kg/m 2 for the control groups. Participant ethnicity varied between the studies and study arms (white: intervention: 12.5%-100%; control: 13.3%-100%) [ 33 - 36 , 38 - 42 ]. Several studies reported on the level of education within their population ranging from 78% of the total sample having a secondary degree [ 36 ], to other studies reporting approximately 20% or above in the usual care and 21% or above in the intervention having a postsecondary education [ 34 , 37 , 38 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations